1983
DOI: 10.1111/j.1442-9993.1983.tb01332.x
|View full text |Cite
|
Sign up to set email alerts
|

The feeding ecology of the dingo II. Dietary and numerical relationships with fluctuating prey populations in south‐eastern Australia

Abstract: The dietary and predator-prey relationships of Canis familiaris dingo were studied for 9 yr at a coastal site and for 1.5 yr at a montane site in south-eastern Australia. The percentage occurrences of items eaten were obtained from faeces, and the abundances of prey by counting waterbirds, trapping small mammals, and tracking large and medium-sized mammals on specially prepared soil plots. Dingoes were also estimated by tracking.The diet was broad but predominantly mammalian (23 species). Dietary frequencies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 28 publications
8
94
0
Order By: Relevance
“…Cat remains were also found in the gut of one dingo (2 %), and in one faecal sample (1.2 %). Consumption of cats by dingoes has also been reported by Newsome, Catling & Corbett (1983), Lundie-Jenkins, Corbett & Phillips (1993), Thomson (1992), Corbett (1995) and Paltridge (2002). In addition, Pettigrew (1993) reported that an adult cat fitted with a radio collar was killed by a dingo.…”
Section: Evidence For Interactions (1 ) Interactions Between Natmentioning
confidence: 77%
“…Cat remains were also found in the gut of one dingo (2 %), and in one faecal sample (1.2 %). Consumption of cats by dingoes has also been reported by Newsome, Catling & Corbett (1983), Lundie-Jenkins, Corbett & Phillips (1993), Thomson (1992), Corbett (1995) and Paltridge (2002). In addition, Pettigrew (1993) reported that an adult cat fitted with a radio collar was killed by a dingo.…”
Section: Evidence For Interactions (1 ) Interactions Between Natmentioning
confidence: 77%
“…Foxes may pose a greater threat to these species during severe drought. Newsome et al (1983), for example, observed greater predation pressure on macropods during drought.…”
Section: Vulpes Vulpesmentioning
confidence: 99%
“…The high occurrence of P. tridactylus in the diet is taken as a reflection of an increase in the population size of this species in the forest. It is also possible that the numbers taken in 1981-1982 reflected an increased exposure due to logging and fire at this time (Newsome et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Not only is it cost-effective, it is also one of the most productive methods of surveying mammals in a forest. However, it should be recognised that the abundance of prey may vary from its relative availability (Newsome et al 1983;Catling et al 2001). Other measures of abundance, such as through the use of soil plots along transects (e.g., Catling and Burt 1994) are valuable.…”
Section: Discussionmentioning
confidence: 99%